Implicit time‒accurate solutions on unstructured dynamic grids - Crumpton, P. I.; Giles, M. B. (International journal for numerical methods in fluids, 1997)
In this paper an unstructured multigrid algorithm is used as an iterative solution procedure for the discrete equations arising from an implicit time discretization of the unsteady Euler equations on tetrahedral grids. To calculate unsteady flows due to oscillating boundaries, a novel grid movement algorithm is introduced in which an elliptic equation with a non‒linear diffusion coefficient is used to define the displacement of interior grid nodes. This allows large grid displacements to be calculated in a single step. The multigrid technique uses an edge‒collapsing algorithm to generate a sequence of grids, and a pseudo‒time‒stepping smoother. On the coarser grids, no grid motion is used. Instead, surface normals are rotated consistently and transfer/interpolation weights are based on the time‒averaged grid co‒ordinates. A 2D NACA0012 test case is used to validate the programme. 3D results are presented for the M6 wing and a full aircraft configuration. © 1997 John Wiley & Sons, Ltd.